Do we manage incontinence in children and adults with special needs adequately? ICI‐RS 2014. Issue 2 (February 2016) - von Gontard, Alexander; de Jong, Tom P. V. M.; Rantell, Angie; Nieuwhof‐Leppink, Anka; Badawi, Jasmin Katrin; Cardozo, Linda
Abstract : Aims: To review studies on the associations of incontinence and special needs in children and adults and to outline future directions in research and clinical care. Materials and Methods: A review of literature was conducted. Open questions and future directions were discussed during the ICI‐RS meeting in 2014. Results: Special needs comprise a wide variety of conditions and disabilities. Individuals with special needs carry a greater risk for all types of incontinence. There is a high tendency for incontinence to persist from childhood into adulthood. Many people do not receive adequate medical care for their incontinence. Conclusions: More detailed research is needed, especially in the adult population with special needs. Assessment and treatment of incontinence should be offered routinely to all those with special needs. Neurourol. Urodynam. 35:304–306, 2016 . © 2016 Wiley Periodicals, Inc.